Variação altitudinal da comunidade de invertebrados aquáticos em bromélias dos gêneros Vriesea Gaudich. e Aechmea Wittm. na serra geral do sul do Brasil - Malfatti, Eduardo (2019)
Bromeliads are one of the groups with the greatest taxonomic, morphological and ecological diversity of the Neotropics. Its leaves are arranged in rosette, and in some species, the overlapping of the leaves allows the entrapment of water and organic matter, forming reservoirs that are habitat for various microorganisms. In Brazil, few studies describe the community of these reservoirs or their response to ecological standards. Thus, the objective of this research was to analyze the effect of the altitudinal gradient on the community of eukaryotes present in the reservoirs of four species of Vriesea Gaudich. and of a species of Aechmea (A. gamosepala Wittm.) that occour at diffrent altitudes on a mountain range in Serra Geral of Southern Brazil. The species/altitudes choosen were: V. gigantea (Maquiné – 20m), V. incurvata (Arroio Garapiá – 400m), V. friburgensis e V. platynema (Pró-Mata – 910 e 915m, respectively). For A. gamosepala, two altitudes were selected, according to their occurrance: Garapiá River and Pró-Mata. Three individuals of each species were sampled, twice for each season, over a year. The water from the reservoirs was collected with a Pasteur pipette and placed in falcon tubes to analyze the organisms in vivo and to estimate the specific richness for each of the bromeliads sampled. A total of 45 morphospecies were found in Vriesea species, with Ciliophora being the most representative phylum (53.3%), followed by Arhthropoda (28.8%), Rotifera (6.6%), Annelida, Plathyelminthes (4.4%) and Nematoda (2.2%). The specific richness in V. gigantea was 8.17 morphospecies, and reached its peak at the intermediate level (V. incurvata) with a total average of 10.79. At higher altitudes the richness decreased (8.83 and 8.67 morphospecies for V. platynema and V. friburgensis, respectively). For A. gamosepala, the bromeliads of higher altitudes obtained the highest phyto-elastic richness (8.63 morphospecies) when compared to the intermediate level (8.17). From this study, it is suggested that bromeliads, in addition to shelter different organisms at different life stages and trophic functions, have communities sensitive to altitude variation, being able to be modeled both by the environment, and by in situ characteristics of the bromeliad